Quarterly tax burden in Brazil 1991-1995 A methodological note - Giambiagi, Fábio (Brazilian Journal of Political Economy, 1996)
This note describes the methodology of the quarterly GDP measured at current prices and allows to calculate the quarterly federal government revenues (excluding the Social Security System) / GDP ratio, on a quarterly basis, since 1991. The data show a more agile analysis of the evolution of the fiscal revenues. It is shown that, beginning in 1993, an undeniable increase of the fiscal revenues / GDP ratio has occurred. This movement continued along 1995, despite the end of the Temporary Tax on Financial Transactions (IPMF). Consequently, between 1992 and 1995, the federal government fiscal revenues experienced an increase of almost 3 points of GDP. JEL Classification: H20; H22.